Can Electronic Health Records Validly Estimate the Effects of Health System Interventions Aimed at Controlling Body Weight?. Issue 11 (27th September 2020) - Gallis, John A.; Kusibab, Kristie; Egger, Joseph R.; Olsen, Maren K.; Askew, Sandy; Steinberg, Dori M.; Bennett, Gary
Abstract : Objective: This study aimed to compare weight collected at clinics and recorded in the electronic health record (EHR) with primary study‐collected trial weights to assess the validity of using EHR data in future pragmatic weight loss or weight gain prevention trials. Methods: For both the Track and Shape obesity intervention randomized trials, clinic EHR weight data were compared with primary trial weight data over the same time period. In analyzing the EHR weights, intervention effects were estimated on the primary outcome of weight (in kilograms) with EHR data, using linear mixed effects models. Results: EHR weight measurements were higher on average and more variable than trial weight measurements. The mean difference and 95% CI were similar at all time points between the estimates using EHR and study‐collected weights. Conclusions: The results of this study can be used to help guide the planning of future pragmatic weight‐related trials. This study provides evidence that body weight measurements abstracted from the EHR can provide valid, efficient, and cost‐effective data to estimate treatment effects from randomized clinical weight loss and weight management trials. However, care should be taken to properly understand the data‐generating process and any mechanisms that may affect the validity of these estimates.